Perpetration of Alcohol-Related Aggression by Male and Female College Students: An Examination of Overt and Relational Aggression. Issue 5 (March 2020) - Robertson, Kirsten; Forbes, Sarah; Thyne, Maree
Existing literature exemplifies the relationship between alcohol and overt aggression, especially for adult males. Less clear is the relationship between alcohol and aggression among male and female college students, in particular, the nature of this aggression and the co-occurrence of drinking and aggression on the same day (temporal proximity). This study examines the chronic and temporal nature of males' and females' alcohol-related aggression among college students. Two hundred fourteen students completed a web-based 7-day event-level survey measuring alcohol consumption and perpetration of physical aggression, verbal aggression, anger, and relational aggression over 4 weeks, resulting in 4, 256 observations (days). The global analysis revealed students who are heavy drinkers are more likely to perpetrate all four forms of aggression, whereas the event-level analysis revealed that specific forms of aggression are associated with drinking at the time, while other forms were not linked to drinking occasions. Cross-tabulation revealed males and females were more likely to use verbal and physical aggression when drinking. For females, drinking was also associated with relational aggression and anger. Despite often being overlooked in research on aggression during emerging adulthood, relational aggression was prevalent. Discrepancies between the global and temporal analysis revealed factors other than alcohol might explain the relationship between chronic alcohol consumption and specific forms of aggression. This is one of the first event-level studies to show the temporal relationship between alcohol and relational aggression. The distinctions in the current study, exemplifying the diversity of alcohol-related aggression, are critical for understanding aggressive behavior, potential gender differences, and for developing interventions. The temporal relationship between alcohol and aggression suggests health interventions should target drinking and aggression simultaneously.